2016
DOI: 10.3892/etm.2016.4015
|View full text |Cite
|
Sign up to set email alerts
|

Heart failure modulates electropharmacological characteristics of sinoatrial nodes

Abstract: Abstract. The impact of heart failure (HF) on sinoatrial node (SAN) channel regulation and electropharmacological responses has remained elusive. The present study aimed to investigate the effects of HF on the electrical activity of SANs with and without pharmacological interventions. Action potentials (APs) were recorded in isolated SANs from normal rabbits (control) and those with HF (rapid ventricular pacing for 4 weeks) prior to and after administration of a funny current blocker (ivabradine; 0.1, 0.3, 3 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…Interestingly, although previous studies in animal models have identified a remarkable range of varying, species-specific roles for Nav isoforms in the SAN [14][15][16]30 , our findings demonstrate that Nav channels may contribute very differently to human SAN pacemaking and conduction 15,16,32 . Studies have found that micromolar TTX can depress heart rate in adult mouse 33 and rabbit SAN preparations 34 , providing evidence that cNav can contribute to SAN automaticity in some adult mammalian hearts. However, in contrast to the mouse SAN study 30 , where nanomolar TTX impaired SAN automaticity but did not inhibit conduction, we found that nanomolar TTX impaired intranodal conduction (~250%) with negligible effects on SAN automaticity (~6%) and atrial conduction (~6%) at physiological conditions.…”
Section: Discussionmentioning
confidence: 95%
“…Interestingly, although previous studies in animal models have identified a remarkable range of varying, species-specific roles for Nav isoforms in the SAN [14][15][16]30 , our findings demonstrate that Nav channels may contribute very differently to human SAN pacemaking and conduction 15,16,32 . Studies have found that micromolar TTX can depress heart rate in adult mouse 33 and rabbit SAN preparations 34 , providing evidence that cNav can contribute to SAN automaticity in some adult mammalian hearts. However, in contrast to the mouse SAN study 30 , where nanomolar TTX impaired SAN automaticity but did not inhibit conduction, we found that nanomolar TTX impaired intranodal conduction (~250%) with negligible effects on SAN automaticity (~6%) and atrial conduction (~6%) at physiological conditions.…”
Section: Discussionmentioning
confidence: 95%
“…In a canine model of HF induced by rapid pacing and using optical mapping, SAN bradycardia is associated with suppression of LCR together with the unresponsiveness of Ca 2+ clock to isoproterenol and caffeine stimulation (Shinohara et al, 2010). In a similar rabbit HF model, alterations of SAN electro-pharmacological responses have been related to lower expression of RyR2, as well as inhibition of SERCA reuptake due to altered phosphorylation of PLN (Chang et al, 2017). By contrast, RyR2 expression, along with other Ca 2+ handling proteins, is increased in the SAN but not in atrial tissue in a HF rat model (Yanni et al, 2011).…”
Section: Ryr2 and Sinus Node Dysfunctionmentioning
confidence: 99%
“…The increase in left ventricular end diastolic pressure observed in heart failure patients causes an increase in the intra-atrial pressure and atrial stretch, which results in atrial electrical remodeling and atrial dilatation [ 107 ]. It has been proposed that cellular and tissue alterations caused by heart failure can also cause electrical and structural remodeling of the pacemaker [ 108 ]; the identified mechanisms so far include a decrease in the HCN4 and sodium currents [ 109 , 110 ]. However, it is not clear how malfunction of the ventricular chambers can result in ionic changes of pacemaker cells.…”
Section: Global Cardiac Aging and Pacemaker Dysfunctionmentioning
confidence: 99%